2022
DOI: 10.1111/fare.12722
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, family cohesion, and acculturation gap conflicts among Latinx emerging adults living in the United States

Abstract: Objective This study examined associations of family cohesion and acculturation gap conflicts with depressive symptoms, as well as the moderation effect of family cohesion on the association between acculturation gap conflicts and depressive symptoms among Latinx emerging adults. Background In addition to normative developmental stressors (e.g., making long‐term career decisions), many Latinx emerging adults face additional sociocultural stressors (acculturative stress, ethnic discrimination) that put them at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…We found poorer MH in the students than the non-students, although effect sizes were small (g from − 0.25 to − 0.24) and scores on risk did not show statistically significant group differences despite the large group sizes. These results are similar to those found in two studies conducted in France 16,17 and the USA with a Latinx population 18 , but different to those found in some other studies conducted in developed countries [12][13][14] where the MH of the students was better than non-students. However, those studies reported results after analysing large national surveys and clearly larger and more representative samples of the population.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found poorer MH in the students than the non-students, although effect sizes were small (g from − 0.25 to − 0.24) and scores on risk did not show statistically significant group differences despite the large group sizes. These results are similar to those found in two studies conducted in France 16,17 and the USA with a Latinx population 18 , but different to those found in some other studies conducted in developed countries [12][13][14] where the MH of the students was better than non-students. However, those studies reported results after analysing large national surveys and clearly larger and more representative samples of the population.…”
Section: Discussionsupporting
confidence: 85%
“…The authors claim that the better MH of the students might be the result of increased MH literacy in the students' population contributing to better identification of MH issues 13 and also because they have better access to MH services 14 . On the other side, some studies indicate that student status is associated with poorer MH [15][16][17][18][19] , but just three studies [16][17][18] Measures. Sociodemographic, lifestyle and MH-related characteristics, apart from the status as student or non-student, basic demographic items were gender, age, housing status, financial issues, parenting and caregiver responsibilities.…”
Section: Registration: Clinicaltrialsgov (Nct04596345)mentioning
confidence: 99%
“…The relations under study may operate differently within father–adolescent dyads (Wheeler et al, 2015) and within established immigration destinations (Pasch et al, 2006). Other important moderators to consider include parent and youth gender (Liu et al, 2011; Schofield et al, 2008), family cohesion and familial coping (Rahman et al, 2023; Santiago et al, 2021), and parent ethnic identity socialization and youth ethnic identity (Brittian et al, 2013; Stein et al, 2022). Finally, broader oppressive systems may elicit joint experiences of cultural stress within families, either through direct or vicarious exposure as experiences are shared within the family (Martin Romero & Stein, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Increased exploration of dyadic bicultural competence can have clinical implications beyond clarifying associations between patterns of individual cultural competence and relationship quality. Cultural gaps in close relationships have been associated with symptoms of psychopathology (e.g., depression; Rahman et al, 2022), although much of this work has focused on gaps in dominant cultural competence, rather than gaps in heritage cultural competence or examining both jointly. Examining dyadic bicultural competence, rather than mismatches in cultural competence, may be helpful in identifying patterns of matches or mismatches in cultural competence that may be associated with negative individual psychological outcomes.…”
Section: Hypotheses and Implicationsmentioning
confidence: 99%